Evaluating the use of web versus mobile devices for ePRO reporting and severe symptom responses at 6 cancer centers. Issue 28 (1st October 2022) - Cronin, Christine; Tramontano, Angela; Schrag, Deborah; Wong, Sandra L.; Osarogiagbon, Raymond U.; Hazard-Jenkins, Hannah W.; Dizon, Don S.; Bian, Jessica J; Hassett, Michael J.
Abstract : 241 Background: Monitoring electronic patient-reported outcomes (ePROs) improves quality of life, reduces acute care, and extends survival in cancer patients. Different modalities for collecting ePROs exist. Many efforts focus on mobile apps, but optimal methods for reporting are not well established. We sought to determine whether patient engagement and symptom reporting patterns differed by submission modality. Methods: Through the SIMPRO Consortium, ePRO questionnaires (eSyM) were collected from medical oncology (MO) and surgical (SUR) patients at six health systems between September 2019-March 2022. Questionnaires assessing 12 symptoms plus functional status and overall wellbeing were sent 2-3 times per week via patient portal and made accessible through two modalities: a web platform or mobile device app (mobile). Patterns and predictors of reporting modality were ascertained using descriptive statistics and logistic regression. Results: In total, 6460 patients submitted 47, 736 questionnaires: 74% via web and 26% via mobile. Of 2679 MO responders, 53% reported via web, 0.7% via mobile only, and 43% via both. Older, black, and unemployed MO patients were more likely to report via web only. Of 3781 SUR responders, 55% reported via web, 0.3% via mobile only, and 45% via both. Older and unemployed SUR patients were more likely to report via web only; disabled SUR patients were less likely to use web only. Patients utilizing both modalities reported significantly more moderate-severe symptoms than web only responders [Table]. Conclusions: Very few patients reported via mobile only, which was unexpected in the context of trends toward mobile-based patient engagement. Moderate-severe symptoms were reported more frequently by dual-modality responders. Patients with access to both modalities may be more likely to report symptoms in real-time compared to web-users who may delay reporting until they have access to a device. The resulting difference between web and mobile reporting modalities could be due to age, race, and employment; future studies should assess other factors, such as locality and cellular coverage. This work emphasizes the importance of deploying ePROs via multiple modalities to maximize accessibility and response rates. Clinical trial information: NCT03850912. Cohort characteristics by reporting modality. MO SUR Web Only Both or Mobile Only P-Value Web Only Both or Mobile Only P-Value Age (mean) 66.6 63.9 < 0.0001* 60.7 60 < 0.0001* Sex (% female) 59.5 57.2 0.24 70.6 71.5 0.55 Race (% Caucasian) 81.2 83.7 0.10 94.6 93.6 0.18 Cancer type (%) GI GYN THOR MULTI OTHER UNKNOWN 38.2 18.1 27.9 2.9 8.1 4.9 40.2 15.8 25.9 3.2 7.4 7.4 0.051 41.1 31.2 17.2 1.2 0.0 9.4 40.9 27.2 19.2 1.7 0.0 11.0 0.03 Employment (% working) 23.7 27.6 0.03* 39.6 43.2 0.03* Marital status (% married) 60.4 60.9 0.82 64.7 63.1 0.32 % reporting ≥ 1 moderate-severe symptom 85 90 0.0003* 88 90 0.07 % reporting ≥ 1 severe symptom 33 36 0.09 31 36 0.002*